Capgras syndrome as a psychiatric manifestation in Parkinson’s disease: a case report and literature review - Estrada Bellmann, Ingrid Eloísa; Ulloa Escobar, Yuriria; Barbosa Flores, S. L.; Pech George, R. E.; González Treviño, Raúl S.; Conde Gómez, L.; Marfil Rivera, Alejandro (UANL. Facultad de Medicina, 2015)
We present the case of a 58-year-old male patient who had symptoms of anxiety after witnessing a case of social violence in his community in 2005. After that, he presented symptoms of Parkinson Disease and in 2006 we established this as the main diagnosis. In 2009 he presented neuropsychiatric symptoms such as apathy, anhedonia, social isolation, blunted affect, visual and auditory hallucinations, paranoid delusions, soliloquies, and the false belief that his wife and daughter had been replaced by identical impostors. We established the diagnosis of Capgras Syndrome. This case is clinically relevant because of the presentation of its symptoms, its evolution and its presenting comorbidity.